Optimasi Variasi Jumlah Blade Inlet Turbo dan Outlet Turbo Terhadap Gaya Dorong Pada Prototype Waterjet Thrusther Produk 3D Printing Menggunakan Metode Taguchi - Oktavianto, Mario; Rollastin, Boy; Hasdiansah, Hasdiansah (Jurnal Inovasi Teknologi Terapan, 2024)
Efforts to improve Indonesia's maritime security continue to be increased by carrying out maritime security operations using a patrol fleet. The ability to maneuver well is needed by a ship to carry out encryption and security against enemies. This research aims to find a combination of Waterjet Thrusther ship propulsion system components that produces the most optimal thrust. The Waterjet Thrusther prototype was made using a 3D printing machine with FDM (Fused Deposition Modeling) technology using ST-PLA (Super Tough Polylactic Acid) filament. This research uses the Taguchi method to create an experimental design. The variables used are the number of turbo inlet blades, impeller type, and the number of turbo outlet blades. The test was carried out using tools in the form of a test vessel weighing 8.06 kg with an electric motor drive engine. The results of this test obtained the highest thrust force in the 2nd variation using a 3 blade type 2 impeller, 13 blade turbo inlet, and 13 blade turbo outlet with the lowest thrust force value of 2.231775 N. The 9th variation produced the lowest thrust force of 0,711225 N using Inlet Turbo 15 blades, Impeller 3 blade type 3, and Outlet Turbo 15 blades.